The Effectiveness of Project-Based Learning on Science Process Skills in Chemistry Education: A Research Findings Perspective - Munawwarah, Munawwarah; Side, Sumiati (Journal of Educational Sciences, 2025)
This study aims to explore and analyze the effectiveness of Project- Based Learning (PjBL) in enhancing scientific process skills in chemistry education at the secondary education level. The research employs the Systematic Literature Review (SLR) method, analyzing 16 recent scholarly articles published within the last ten years. The findings indicate that implementing PjBL significantly improves students' scientific process skills, including critical thinking, problem-solving, and data analysis. Additionally, PjBL enhances students' motivation and engagement in the learning process. The reviewed studies suggest that integrating technology into PjBL, such as digital media and STEAM approaches, further strengthens its effectiveness in fostering a deeper understanding of scientific concepts. However, several challenges remain, including the need for teacher training in designing and managing project-based activities effectively, as well as limited learning resources. Therefore, this study recommends enhancing teacher training programs, providing more diverse teaching materials, and ensuring institutional support for the implementation of PjBL. Overall, the study confirms that PjBL is an innovative instructional strategy that optimally develops scientific process skills and can be widely applied in chemistry education.